Contesting Sustainability of Mega-Events in Chinese Metropolises: A Narrative and Practise Review - Li, Lingyue (Frontiers in Sustainable Cities, 2021)
Since the Rio Summit, sustainability has been enshrined in the official claims of mega-events, and scholars' sustainability concerns over mega-events persist. This research is one of the few contextualising the debates in China where mega-events have become prevalent and contributed to metropolitan boosterism since the 1990s. It argues that the ill-defined, ambiguous meaning of sustainability leaves room for host cities to discursively strike a balance between environment protection, social equity and economic growth, but unavoidably leads to paradoxes of sustainability in actual practises. The argument is supported by a longitudinal study on 12 major mega-events held or to be held in Chinese metropolises. Narratively, Chinese government's articulation of sustainability declared by international organisations of top mega-events has evolved technocratic and inclusive. Practically, amongst the three variants of sustainability, economic sustainability, and environmental sustainability appear to work better than social sustainability. Findings of this research call for clarified narratives and concrete measures to guide mega-event practises.